2012
DOI: 10.1111/j.1532-5415.2012.04052.x
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Glycemic Control and Hip Fracture

Abstract: The present study found an association between tight glycemic control (when HbA1c < 7%) and greater risk of hip fracture in individuals being treated for type 2 diabetes mellitus. Greater caution needs to be exercised in treating older patients with diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 23 publications
(37 reference statements)
0
65
0
3
Order By: Relevance
“…Generally, special attention is needed to prevent hypoglycemia, especially in elderly patients, because severe hypoglycemia is more likely to occur in these patients 15 , and hypoglycemia may induce cognitive dysfunction and the risk of fracture in elderly patients 16,17 . In this PMS of canagliflozin, five patients, who received other anti-diabetics concomitantly such as insulin preparations, sulfonylureas, and/or glynides, for which the association with hypoglycemia is widely known 18 , experienced a hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, special attention is needed to prevent hypoglycemia, especially in elderly patients, because severe hypoglycemia is more likely to occur in these patients 15 , and hypoglycemia may induce cognitive dysfunction and the risk of fracture in elderly patients 16,17 . In this PMS of canagliflozin, five patients, who received other anti-diabetics concomitantly such as insulin preparations, sulfonylureas, and/or glynides, for which the association with hypoglycemia is widely known 18 , experienced a hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Hip fracture which is a direct cause of disability and frailty is also associated with hypoglycemia. In a case control study of 932 participants with diabetes and hip fracture, mean (SD) age 77.3 (7.7) years, matched for age, sex, race, duration of diabetes mellitus and comorbidities with a similar number of control subjects, participants with tighter glycemic control (HbA1c < 6% and 6.1-7.0%) were more likely to have a hip fracture than those with HbA1c >8% (OR 3.01, 95% CI 2.01 to 4.51, P < .001; and 2.34, 1.71 to 3.22, P < .001, respectively) [24]. In a case control study, insulin treatment was significantly associated with bone fractures in men (OR 3.20, 95% CI 1.32 to 7.74) maintained after adjusting for concomitant hypoglycemic medications.…”
Section: Physical Dysfunctionmentioning
confidence: 99%
“…Even though studies have proven the association between hip fracture risk and type 2 diabetic patients, there are inconsistencies present in the association between glycemic control on hip fracture in diabetic patients [19][20][21][22]. Studies have shown a greater risk of hip fracture in a variety of glycemic control including tight glycemic control [19] and inadequate glucose control [21,22]. On the contrary, a previous study even suggested intensive glycemic control when compared to standard control is not associated with an increase or decrease in fracture risk [20].…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies suggested type 2 diabetes was associated with increased risk of hip fracture [5]. Even though studies have proven the association between hip fracture risk and type 2 diabetic patients, there are inconsistencies present in the association between glycemic control on hip fracture in diabetic patients [19][20][21][22]. Studies have shown a greater risk of hip fracture in a variety of glycemic control including tight glycemic control [19] and inadequate glucose control [21,22].…”
Section: Discussionmentioning
confidence: 97%